Peran eWOM dan Gaya Hidup Hedonis terhadap Keputusan Pembelian KFC pada Generasi Z di Kota Gorontalo - Altav Rian Kurniawan; Rizan Machmud; Djoko Lesmana Radji (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the influence of electronic word of mouth (eWOM) and hedonic lifestyle on the purchasing decisions of Generation Z consumers of KFC in Gorontalo City. A quantitative research approach was employed using a survey method, and the data were analyzed using SPSS version 25. The research sample consisted of Generation Z consumers who had purchased KFC products. Hypothesis testing was conducted through multiple linear regression analysis to examine both partial and simultaneous effects among the variables. The findings reveal that eWOM has a positive and significant effect on purchasing decisions. This indicates that favorable online reviews, recommendations, and digital information enhance consumer confidence and increase their likelihood of purchasing KFC products. Furthermore, hedonic lifestyle was also found to have a positive and significant effect on purchasing decisions, suggesting that the pursuit of pleasure, social experiences, and trend-following behavior plays an important role in shaping consumption patterns among Generation Z consumers. Simultaneously, eWOM and hedonic lifestyle exert a positive and significant influence on purchasing decisions, accounting for 55.4% of the variance in consumer purchasing decisions. These findings provide empirical evidence that successful marketing strategies targeting Generation Z depend not only on product quality but also on effective digital communication and a comprehensive understanding of consumers’ lifestyle characteristics.